2009
DOI: 10.1038/onc.2008.500
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor-dependent cyclooxygenase-2 induction in gliomas requires protein kinase C-δ

Abstract: Earlier, we showed that epidermal growth factor receptor (EGFR) signaling in human glioma cells increased cyclooxygenase-2 (COX-2) expression through p38-mitogen-activated protein kinase (MAPK)-dependent activation of the Sp family of transcription factors. Further mechanistic details of EGFR-dependent induction of COX-2 expression in glioma cells remained elusive. Protein kinase Cs (PKCs) comprise a family of serine-threonine kinases that are major mediators of signaling from receptor tyrosine kinases. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 49 publications
5
25
0
1
Order By: Relevance
“…In fact, blocking this transcription factor with mithramycin A or siRNA significantly inhibits p38-MAPK-dependent VEGF promoter activation and expression. These results are consistent with our previous findings that EGF-dependent activation of the p38-MAPK signaling pathway positively regulates Sp1 activity and further increases COX-2 expression in glioma cells (18,28). Here, the EGFR/p38-MAPK/Sp1 signaling axis similarly increases VEGF levels, confirming the importance of this pathway in VEGF regulation.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In fact, blocking this transcription factor with mithramycin A or siRNA significantly inhibits p38-MAPK-dependent VEGF promoter activation and expression. These results are consistent with our previous findings that EGF-dependent activation of the p38-MAPK signaling pathway positively regulates Sp1 activity and further increases COX-2 expression in glioma cells (18,28). Here, the EGFR/p38-MAPK/Sp1 signaling axis similarly increases VEGF levels, confirming the importance of this pathway in VEGF regulation.…”
Section: Discussionsupporting
confidence: 82%
“…We previously found that EGF-induced COX-2 expression in glioma cells required p38-MAPK-dependent activation of the Sp1 transcription factor (18,28). VEGF expression is similarly induced by EGF in various systems (29)(30)(31).…”
Section: Celecoxib Induce Vegf Mrna Expression At Levels Comparable Tmentioning
confidence: 99%
“…51,52 In particular, the p38 MAP kinase is phosphorylated and activated by RA treatment in NB4 cells 53 and PRKCD phosphorylation at Thr505 was recently shown to be dependent upon p38. 54 However, RA activates many complex signaling cascades that may also lie upstream of PRKCD and TOP2B. Indeed, future directions will aim to elucidate more clearly the entire signaling pathway leading to TOP2B regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Non-steroidal anti-inflammatory agents (NSAIDs) target Cox-2 and PKC delta, a prosurvival pathway both in cancer [66] and the heart [65] and interfere with this infarct-sparing mechanism. Cox-2/EGFR/MAPK signal cascade acts in cancer [67] as well as being a pro-hypertrophic mechanism in the heart [68].…”
Section: Addressing Therapeuticsmentioning
confidence: 99%